A Model of Perinatal Ischemic Stroke in the Rat: 20 Years Already and What Lessons? - Charriaut-Marlangue, Christiane; Baud, Olivier (Frontiers in Neurology, 2018)
Neonatal hypoxia-ischemia (HI) and ischemia are a common cause of neonatal brain injury resulting in cerebral palsy with subsequent learning disabilities and epilepsy. Recent data suggest a higher incidence of focal ischemia-reperfusion located in the middle cerebral artery (MCA) territory in near-term and newborn babies. Pre-clinical studies in the field of cerebral palsy research used, and still today, the classical HI model in the P7 rat originally described by Rice et al. (1). At the end of the 90s, we designed a new model of focal ischemia in the P7 rat to explore the short and long-term pathophysiology of neonatal arterial ischemic stroke, particularly the phenomenon of reperfusion injury and its sequelae (reported in 1998). Cerebral blood-flow and cell death/damage correlates have been fully characterized. Pharmacologic manipulations have been applied to the model to test therapeutic targets. The model has proven useful for the study of seizure occurrence, a clinical hallmark for neonatal ischemia in babies. Main pre-clinical findings obtained within these 20 last years are discussed associated to clinical pattern of neonatal brain damage.